Successful Expectant Management of the Anomalous Fetus with Sirenomelia in Twin Pregnancy: A Case Report and Literature Review - Tilahun, Temesgen (Int Med Case Rep J, 2021)
BACKGROUND: Sirenomelia is a rare congenital defect. Its management during pregnancy and after delivery is becoming a controversial issue because of its complex nature and management outcome. The possibility of expectant management in the sirenomelia twin drove us to write this case report. CASE PRESENTATION: We report a case of successful expectant management in twin sirenomelia which was diagnosed in the second trimester. Prenatal counseling of the couple by a multi-disciplinary team regarding the diagnosis, treatment, and prognosis of the sirenomelia twin was done. The mother gave birth, at term, to one normal and one sirenomelia neonate by cesarean section. CONCLUSION: Expectant management of sirenomelia one in twin pregnancy is advisable in a resource-limited setting.